Role of nanotechnology in dentistry: a systematic review - Raj, Akanksha; J. Shetty, Neetha; Atif, Ali (Journal of Stomatology, 2023)
Nanotechnology involves physical, chemical, and biological properties of nanoscale structures and their components. Nanotechnology is based on the principle of manipulating atoms and molecules one by one, to create usable structures. Many advances in health sciences as well as materials’ science, biotechnology, electronic and computer technology, aviation, and space exploration would be possible because of this technology. The objective of the study was to conduct a systematic review of the literature to evaluate the applications of nano-technology in dentistry. Included studies were systematically analyzed based on PRISMA (preferred reporting items for systematic reviews and meta-analyses), and studies were identified based on PICO (glossary of evidence-based terms, 2007): random clinical trials (RCT), which have been published in last 6 years and in English language only. Electronic database search of PubMed, Medline, Cochrane, and clinicaltrials.gov was performed using MeSH terms: nanotechnology, nanotechnology in dentistry, and nanotechnology in dental practice. Articles published between 2014-2020 were reviewed, and were included based on inclusion and exclusion criteria. The authors assessed individual study bias by using Cochrane risk of bias tool to find bias risk assessment. Based on this systematic review of literature, it can be concluded that advancement in nanotechnology has significantly influenced dental disease prevention and therapy.